Adsorbent and preparation method and application thereof
Through the harmonization and alkali metal ion exchange technology of molecular sieve, phthalite, alumina and alkali metal ion exchange technology, the adsorption capacity and regeneration capacity of the adsorbent are improved, and the problems of low adsorbent adsorption capacity and olefin polymerization are solved.
Patent Information
- Application Number
- CN202111156685.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-09-30
AI Technical Summary
In the prior art, the adsorption capacity of the adsorbent is low, cannot be regenerated, and the adsorption and exothermic heat is obvious, which can easily cause the problem of olefin polymerization.
The solution of molecular sieve, phthalite and alumina blending is adopted to reduce proton acid exchange through ion exchange of alkali metal/alkaline earth metal solution, and reduce the amount of molecular sieve, and improve the adsorption capacity and regeneration ability of the adsorbent.
The adsorption capacity of the adsorbent is increased, and the carbon deposit is less after multiple regeneration, reducing the risk of olefin polymerization during the adsorption process.
Abstract
Description
Technical Field
[0001] The invention relates to an adsorbent and a preparation method thereof and application of the adsorbent in removing polar compounds from olefins. Background Art
[0002] C2-C4 low-carbon olefins such as ethylene, propylene, and butene are important industrial raw materials and are basic raw materials for synthesizing high value-added chemical products such as polyolefins, ethylene oxide, propylene oxide, bisphenol A, polycarbonate, etc. However, various impurities such as basic nitrogen, sulfur, and oxygen-containing compounds are commonly found in these chemical raw materials. The presence of these impurities can cause poisoning of downstream catalysts, reduce the quality of downstream products, and prevent the device from operating stably and safely. Therefore, it is necessary to design a purification unit in the reaction system to purify the olefin raw materials through adsorbents to protect the main catalyst and maintain stable operation of the device. The development of efficient adsorbents is of great significance.
[0003] CN102451746 A discloses a modified 13X zeolite molecular sieve nitrogen oxide purification catalyst and a preparation method. The mass percentage composition of the nitrogen oxide purification catalyst is: 52.17-89.11% of 13X zeolite molecular sieve, 9.9-34.78% of γ-alumina (γ-A12O3), and 0.99-13.05% of metal oxides. The nitrogen oxide purification catalyst prepared by the invention uses a mixture of 13X zeolite molecular sieve and γ-alumina (γ-A12O3) as a carrier, is impregnated with an equal volume of a metal nitrate solution, and is dried and calcined to obtain the catalyst. The purification catalyst is used to catalyze the conversion of nitrogen oxides.
[0004] CN105457600A discloses a method for preparing a denitrification adsorbent, which is an adsorbent obtained by treating a fluorine-containing mixed acid complex liquid with a molecular sieve as a carrier, and the adsorbent has improved polarity and acidity, thereby facilitating the removal of nitrogen-containing compounds. The adsorbent is used for removing nitrogen-containing compounds from naphtha.
[0005] CN103418164B discloses a method for removing oxygen-containing compounds from a hydrocarbon flow. The method removes oxygen-containing compound impurities from a hydrocarbon flow by using a porous metal organic compound as a solid adsorbent. The solid adsorbent is a porous metal organic compound, and its chemical composition formula is M3(BTC)2(L)3m, wherein M is a transition metal element selected from at least one of Cu, Co, Fe, Ni, Zn, and Cr, BTC represents deprotonated trimesic acid, L is a solvent molecule selected from at least one of H2O, NH3, CH3OH, DMF, THF, and C2H5OH, and m represents the average number of solvent molecules bound to each metal ion, and 0≦m≦1.
[0006] However, in the process of removing polar compounds such as nitrogen-containing compounds, sulfur and oxygen-containing compounds, the existing technology still has problems such as low adsorption capacity of the adsorbent, inability to regenerate the adsorbent, large solid waste emissions, obvious adsorption exotherm, and easy to cause olefin polymerization. Summary of the invention
[0007] The purpose of the present invention is to solve the problems in the prior art that the adsorbent has low adsorption capacity, cannot be regenerated, has obvious adsorption heat release, and is easy to cause olefin polymerization. Provide an adsorbent and a preparation method thereof. The adsorbent adopts a solution of molecular sieve, pseudo-boehmite, and alumina, and can further exchange proton acid through ion exchange with an alkali metal / alkaline earth metal solution, and can further reduce the amount of molecular sieve used, while the adsorption capacity of the adsorbent is not reduced, and the amount of carbon deposits of the adsorbent is less after multiple regenerations.
[0008] According to the first aspect of the present invention, the present invention provides an adsorbent, which contains: a metal component, a molecular sieve, pseudo-boehmite and alumina, the B acid / L acid is below 0.1, and the metal component is selected from an alkali metal component and / or an alkaline earth metal component.
[0009] According to a second aspect of the present invention, the present invention provides a method for preparing the adsorbent of the present invention, the method comprising:
[0010] 1) kneading and extruding molecular sieve, pseudo-boehmite, alumina, peptizing agent and extrusion aid, drying and calcining to obtain adsorbent original particles A;
[0011] 2) Add the adsorbent original particles A to a solution containing an alkali metal component compound and / or an alkaline earth metal component compound, perform ion exchange, filter, wash and dry to obtain the adsorbent.
[0012] According to a third aspect of the present invention, the present invention provides use of the adsorbent of the present invention for removing polar compounds from olefins; preferably, the olefins are C2-C4 olefins, preferably one or more of ethylene, propylene and butene, and the polar compounds are selected from one or more of H2O, methanol, ammonia, H2S and COS.
[0013] The adsorbent of the present invention is a reasonable combination of metal components, molecular sieves, pseudo-boehmite and alumina. The molecular sieve is mainly microporous and has a strong electrostatic field, while the pseudo-boehmite and alumina are mainly mesoporous, providing excellent diffusion performance for the adsorbent. Alkali metal modification can reduce the amount of B acid in the adsorbent, reduce the surface activity of the adsorbent, and reduce the risk of olefin polymerization during the adsorption process. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0015] The present invention provides an adsorbent, which contains: a metal component, a molecular sieve, pseudo-boehmite and alumina, wherein the Br acid / L acid ratio is less than 0.1, and the metal component is selected from an alkali metal component and / or an alkaline earth metal component. The adsorbent having the above-mentioned characteristics of the present invention has a large adsorption capacity, and the amount of Br acid is reduced, the surface activity of the adsorbent is reduced, and the risk of olefin polymerization is reduced.
[0016] According to a preferred embodiment of the present invention, the B acid / L acid ratio of the adsorbent is 0.001-0.095, preferably 0.03-0.08, thereby further increasing the adsorption capacity of the adsorbent and reducing the surface activity of the adsorbent.
[0017] According to a preferred embodiment of the present invention, the adsorbent contains: 0.002-1% by weight of metal component calculated as metal oxide, 5-30% by weight of molecular sieve, 20-50% by weight of pseudo-boehmite, and 20-50% by weight of alumina; thereby, the adsorption capacity of the adsorbent can be further increased and the surface activity of the adsorbent can be reduced.
[0018] According to a preferred embodiment of the present invention, preferably, the adsorbent contains: 0.01-0.8 wt % of metal component calculated as metal oxide, 10-25 wt % of molecular sieve, 30-45 wt % of pseudo-boehmite, and 30-45 wt % of alumina; thereby, the adsorption capacity of the adsorbent can be further increased and the surface activity of the adsorbent can be reduced.
[0019] According to a preferred embodiment of the present invention, preferably, the metal component is selected from one or more of sodium, potassium and calcium.
[0020] According to a preferred embodiment of the present invention, preferably, the molecular sieve is selected from one or more of X-type molecular sieve and Y-type molecular sieve; preferably selected from one or more of 13X molecular sieve and NaY molecular sieve. The aforementioned preferred molecular sieve is used, thereby further improving the adsorption capacity of the adsorbent.
[0021] The adsorbents having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to the present invention, the preparation method of the adsorbent described in the present invention is improved, and the method comprises:
[0022] 1) kneading and extruding molecular sieve, pseudo-boehmite, alumina, peptizing agent and extrusion aid, drying and calcining to obtain adsorbent original particles A;
[0023] 2) Adding the adsorbent original particles A to a solution containing an alkali metal component compound and / or an alkaline earth metal component compound, ion exchange, filtering, washing, and drying to obtain the adsorbent. The present invention further reduces the amount of protonic acid through alkali metal exchange, and can reduce propylene polymerization caused by heat release.
[0024] According to a preferred embodiment of the present invention, in step 1), the calcination conditions include: a temperature of 200 to 400° C., preferably 300 to 350° C. The aforementioned preferred calcination method can further increase the adsorption capacity of the adsorbent.
[0025] According to a preferred embodiment of the present invention, in step 1), the calcination conditions include: a time of 2 to 10 hours, preferably 4 to 6 hours.
[0026] According to a preferred embodiment of the present invention, in step 2), the drying conditions include: a temperature of 50 to 150°C.
[0027] According to a preferred embodiment of the present invention, in step 2), the drying conditions include: time is 2-12 hours.
[0028] According to a preferred embodiment of the present invention, the conditions for ion exchange include: ion exchange at room temperature for 2 to 5 hours.
[0029] According to a preferred embodiment of the present invention, the alkali metal component compound and / or alkaline earth metal component compound may be selected from a wide range of types, and for the present invention, it is preferably selected from one or more of nitrates, carbonates, acetates and hydroxides. In the embodiments of the present invention, sodium hydroxide is used as an example for illustration, but the scope of the present invention cannot be limited thereby.
[0030] According to a preferred embodiment of the present invention, the solid-liquid mass ratio of the adsorbent original particles A to the solution containing the alkali metal component compound and / or the alkaline earth metal component compound is 0.3-0.1.
[0031] According to a preferred embodiment of the present invention, the concentration of the solution containing the alkali metal component compound and / or the alkaline earth metal component compound is 0.02-0.5 wt %, preferably 0.1-0.4 wt %.
[0032] According to a preferred embodiment of the present invention, the method of the present invention includes: a) the preparation of the pseudo-boehmite includes: adding 0.5mol / L to 1.5mol / L sodium aluminate solution and 0.5mol / L to 1.5mol / L nitric acid solution in parallel, controlling the reaction pH to 6 to 8, the reaction temperature to 40 to 90°C, the reaction time to 0.5 to 3 hours, obtaining a precipitate, washing and drying the precipitate to obtain pseudo-boehmite. The pseudo-boehmite prepared by the aforementioned method is used in the present invention to further improve the mechanical strength and capacity of the adsorbent.
[0033] According to a preferred embodiment of the present invention, the method of the present invention includes: b) the preparation of the alumina includes: uniformly mixing pseudo-boehmite and polyacrylic acid solution, drying, and roasting; the preparation of the pseudo-boehmite preferably used includes: adding 0.5mol / L to 1.5mol / L sodium aluminate solution and 0.5mol / L to 1.5mol / L nitric acid solution in parallel, controlling the reaction pH to 6 to 8, the reaction temperature to 40 to 90°C, the reaction time to 0.5 to 3 hours, obtaining a precipitate, and washing and drying the precipitate. This can further increase the adsorption capacity of the adsorbent.
[0034] According to a preferred embodiment of the present invention, preferably, the mass concentration of the polyacrylic acid solution in step b) is 0.5-1.5%, thereby further improving the adsorption capacity of the adsorbent.
[0035] According to a preferred embodiment of the present invention, preferably, the solid-liquid mass ratio of pseudo-boehmite to the polyacrylic acid solution is 1:0.5-1.5, thereby further improving the adsorption capacity of the adsorbent.
[0036] The present invention provides an application of the adsorbent of the present invention for removing polar compounds from olefins; preferably, the olefins are C2-C4 olefins, more preferably one or more of ethylene, propylene and butene, and the polar compounds are selected from one or more of H2O, methanol, ammonia, H2S and COS.
[0037] The adsorbent of the present invention can be used to remove polar compounds from olefins. It is preferably used to remove polar compounds such as H2O, methanol, ammonia, H2S, COS, etc. from low-carbon olefins such as ethylene, propylene, butene, etc. In the embodiments of the present invention, the adsorption of ammonia and H2S is used as an exemplary description.
[0038] The present invention will be further described below by way of examples.
[0039] The acid center of the sample was tested by NH3-TPD on a PX200A programmed temperature thermal desorption device of Tianjin Pengxiang Technology Co., Ltd. The ammonia adsorption temperature was 100 °C, the carrier gas was He, and the flow rate was 30 mL min -1 , heating rate is 10℃·min-1 The acid center with a temperature less than 300℃ is a weak acid center, and the acid center with a temperature greater than 300℃ is a strong acid center. The total acid content is obtained by microbalance. The acid content of strong acid center and weak acid center is obtained by integral fitting.
[0040] Nicolet 380 FT-IR was used to determine the B acid and L acid of the sample. The scanning range was (4 000-1 300) cm-1, the resolution was 4.0 cm-1, and about 8 mg of the sample was taken at 400 °C with a 1.33×10 -2 After Pa vacuum dehydration for 2 hours, the temperature was lowered to 200℃ for sample bulk scanning, pyridine was adsorbed for 5 minutes, and after equilibrium, vacuum was evacuated for 0.5 hours to remove unabsorbed pyridine. Finally, infrared scanning was carried out at 200℃, 300℃ and 400℃ respectively.
[0041] Sample surface activity determination: 20 mg of adsorbent was loaded into a pulse microreactor, the reactor temperature was 300°C, 1-hexene was used as the probe molecule, the injection volume was 0.4 μL, and the reaction product was detected by Agilent gas phase. 1-hexene conversion rate = 1-1-hexene content in the product. The higher the 1-hexene conversion rate, the higher the surface activity, and the lower the 1-hexene conversion rate, the lower the surface activity.
[0042] Comparative Example 1
[0043] 10 kg of 13X (purchased from Jianlong Micro-Nano), 15 kg of pseudo-boehmite (purchased from Jiangsu Sanji Chemical Additive Factory), 15 kg of alumina (purchased from Shandong Yuneng) and 0.3 kg of sesbania powder were powdered and mixed evenly, and then 5 kg of HNO3 aqueous solution (3 wt%) was added and kneaded. After kneading, the mixture was extruded and dried at 120°C for 12 hours. The extruded sample was calcined at 300°C for 5 hours to obtain the adsorbent. The adsorbent B acid / L acid was 0.21, and the 1-hexene conversion rate at 300°C was 80%, which shows that a higher B acid content will lead to a higher 1-hexene conversion rate and a high surface activity of the adsorbent.
[0044] Determination of the adsorption amount of NH3 and H2S on the adsorbent: 5g of adsorbent was loaded into a fixed bed reactor, and nitrogen containing 1000ppmNH3 and 1000ppmH2S was used as raw gas respectively. The room temperature was 20℃, normal pressure, and the flow rate was 100ml / min. The content of H2S and NH3 in the outlet gas was determined by a sulfur-nitrogen analyzer. When the content of NH3 and H2S in the outlet gas exceeded 1ppm, it was regarded as adsorbent breakthrough. The breakthrough adsorption amount of NH3 calculated by the breakthrough curve was 2.8%, and the breakthrough adsorbent amount of H2S was 1.5%.
[0045] Example 1
[0046] 10 kg of 13X (purchased from Jianlong Micronano), 15 kg of pseudo-boehmite (purchased from Jiangsu Sanji Chemical Additive Factory, not specifically stated, the same as in the following examples), 15 kg of alumina (purchased from Shandong Yuneng, not specifically stated, the same as in the following examples) and 0.3 kg of sesbania powder were powdered and mixed evenly, and then 5 kg of HNO3 aqueous solution (3 wt%) was added and kneaded. After kneading, the mixture was extruded into strips and dried at 120°C for 12 hours. The extruded sample was calcined at 300°C for 5 hours to obtain the original adsorbent particles. 10 kg of the original adsorbent particles were exchanged with 50 kg of 0.2 wt% NaOH solution for 3 hours, filtered, and dried at 100°C to obtain the adsorbent. The adsorbent B acid / L acid is 0.08, and the 1-hexene conversion rate at 300°C is 1.8%. This shows that after the alkaline solution exchange, the B acid content of the sample is reduced, the 1-hexene conversion rate is low, and the adsorbent surface activity is low.
[0047] Determination of the adsorption amount of NH3 and H2S on the adsorbent: 5g of adsorbent was loaded into a fixed bed reactor, and nitrogen containing 1000ppmNH3 and 1000ppmH2S was used as raw gas respectively. The room temperature was 20℃, normal pressure, and the flow rate was 100ml / min. The content of H2S and NH3 in the outlet gas was determined by a sulfur-nitrogen analyzer. When the content of NH3 and H2S in the outlet gas exceeded 1ppm, it was regarded as adsorbent breakthrough. The breakthrough adsorption amount of NH3 calculated by the breakthrough curve was 3.0%, and the breakthrough adsorbent amount of H2S was 1.7%.
[0048] Example 2
[0049] 10 kg of 13X, 20 kg of pseudo-boehmite, 10 kg of alumina and 0.3 kg of sesbania powder were powdered and mixed evenly, and then 5 kg of HNO3 aqueous solution (3 wt%) was added and kneaded. After kneading, the mixture was extruded into strips and dried at 120°C for 12 hours. The extruded strips were calcined at 350°C for 5 hours to obtain the original adsorbent particles. 10 kg of the original adsorbent particles were exchanged with 50 kg of 0.1 wt% NaOH solution for 3 hours, filtered and dried at 80°C to obtain the adsorbent. The adsorbent B acid / L acid was 0.05, and the 1-hexene conversion rate at 300°C was 0.4%. This indicates that the B acid content is low, the 1-hexene conversion rate is low, and the adsorbent surface activity is low.
[0050] Determination of the adsorption amount of NH3 and H2S on the adsorbent: 5g of adsorbent was loaded into a fixed bed reactor, and nitrogen containing 1000ppmNH3 and 1000ppmH2S was used as raw gas respectively. The room temperature was 20℃, normal pressure, and the flow rate was 100ml / min. The content of H2S and NH3 in the outlet gas was determined by a sulfur-nitrogen analyzer. When the content of NH3 and H2S in the outlet gas exceeded 1ppm, it was regarded as adsorbent breakthrough. The breakthrough adsorption amount of NH3 calculated by the breakthrough curve was 2.9%, and the breakthrough adsorbent amount of H2S was 1.7%.
[0051] Example 3
[0052] 10 kg of 13X, 10 kg of pseudo-boehmite, 20 kg of alumina and 0.3 kg of sesbania powder were powdered and mixed evenly, and then 5 kg of HNO3 aqueous solution (3 wt%) was added and kneaded. After kneading, the mixture was extruded into strips and dried at 120°C for 12 hours. The extruded strips were calcined at 350°C for 5 hours to obtain the original adsorbent particles. 10 kg of the original adsorbent particles were exchanged with 50 kg of 0.4% NaOH solution for 3 hours, filtered and dried at 120°C to obtain the adsorbent. The adsorbent B acid / L acid was 0.05, and the 300°C 1-hexene conversion rate was 0.7%. This shows that when the alumina content is high, the B acid content of the sample is reduced after the alkaline solution exchange, the 1-hexene conversion rate is low, and the adsorbent surface activity is low.
[0053] Determination of the adsorption amount of NH3 and H2S on the adsorbent: 5g of adsorbent was loaded into a fixed bed reactor, and nitrogen containing 1000ppmNH3 and 1000ppmH2S was used as raw gas respectively. The room temperature was 20℃, normal pressure, and the flow rate was 100ml / min. The content of H2S and NH3 in the outlet gas was determined by a sulfur-nitrogen analyzer. When the content of NH3 and H2S in the outlet gas exceeded 1ppm, it was regarded as adsorbent breakthrough. The breakthrough adsorption amount of NH3 calculated by the breakthrough curve was 3.2%, and the breakthrough adsorbent amount of H2S was 3.0%.
[0054] Example 4
[0055] Add 200 ml of distilled water to a co-precipitation reactor (2000 ml), add a 1.0 mol / L sodium aluminate solution at a rate of 10 ml / min, and add a 1.0 mol / L nitric acid solution at the same time. Control the addition rate of the nitric acid solution so that the pH is 8 for reaction. The reaction temperature is 50°C and the reaction time is 1 hour to obtain a precipitate. Wash and dry the precipitate to obtain pseudo-boehmite.
[0056] 10 kg of 13X, 15 kg of pseudo-boehmite prepared by the above scheme, 15 kg of alumina and 0.3 kg of sesbania powder were powdered, mixed evenly, and then 5 kg of HNO3 aqueous solution (3 wt%) was added and kneaded. After kneading, the mixture was extruded into strips and dried at 120°C for 12 hours. The extruded strips were roasted at 300°C for 5 hours to obtain the original adsorbent particles. 10 kg of the original adsorbent particles were exchanged with 50 kg of 0.2 wt% NaOH solution for 3 hours, filtered and dried at 100°C to obtain the adsorbent. The adsorbent B acid / L acid was 0.03, and the 300°C 1-hexene conversion rate was 0.2%. This shows that after the alkaline solution exchange, the B acid content of the sample was reduced, the 1-hexene conversion rate was low, and the adsorbent surface activity was low.
[0057] Determination of the adsorption amount of NH3 and H2S on the adsorbent: 5g of adsorbent was loaded into a fixed bed reactor, and nitrogen containing 1000ppmNH3 and 1000ppmH2S was used as raw gas respectively. The room temperature was 20℃, normal pressure, and the flow rate was 100ml / min. The content of H2S and NH3 in the outlet gas was determined by a sulfur-nitrogen analyzer. When the content of NH3 and H2S in the outlet gas exceeded 1ppm, it was regarded as adsorbent breakthrough. The breakthrough adsorption of NH3 calculated by the breakthrough curve was 3.5%, and the breakthrough adsorption of H2S was 2.0%.
[0058] Example 5
[0059] Add 200 ml of distilled water to a co-precipitation reactor (2000 ml), add a 1.0 mol / L sodium aluminate solution at a rate of 10 ml / min, and add a 1.0 mol / L nitric acid solution at the same time. Control the addition rate of the nitric acid solution so that the pH is 8 for reaction. The reaction temperature is 50°C and the reaction time is 1 hour to obtain a precipitate. Wash and dry the precipitate to obtain pseudo-boehmite.
[0060] Take 20 kg of the aforementioned pseudo-boehmite, add 20 kg of a polyacrylic acid solution with a mass concentration of 1.0%, mix well, dry at 100° C. for 8 hours, and calcine at 550° C. for 6 hours to obtain alumina.
[0061] 10 kg of 13X, 15 kg of pseudo-boehmite (purchased from Jiangsu Sanji Chemical Additive Factory), 15 kg of alumina prepared by the above scheme and 0.3 kg of sesbania powder were powdered, mixed evenly, and then 5 kg of HNO3 aqueous solution (3 wt%) was added and kneaded. After kneading, the mixture was extruded and dried at 120°C for 12 hours. The extruded sample was calcined at 300°C for 5 hours to obtain the original adsorbent particles. 10 kg of the original adsorbent particles were exchanged with 50 kg of 0.2 wt% NaOH solution for 3 hours, filtered and dried at 100°C to obtain the adsorbent. The adsorbent B acid / L acid was 0.04, and the 300°C 1-hexene conversion rate was 0.3%. This shows that after the alkaline solution exchange, the B acid content of the sample is reduced, the 1-hexene conversion rate is low, and the adsorbent surface activity is low.
[0062] Determination of the adsorption amount of NH3 and H2S on the adsorbent: 5g of adsorbent was loaded into a fixed bed reactor, and nitrogen containing 1000ppmNH3 and 1000ppmH2S was used as raw gas respectively. The room temperature was 20℃, normal pressure, and the flow rate was 100ml / min. The content of H2S and NH3 in the outlet gas was determined by a sulfur-nitrogen analyzer. When the content of NH3 and H2S in the outlet gas exceeded 1ppm, it was regarded as adsorbent breakthrough. The breakthrough adsorption amount of NH3 calculated by the breakthrough curve was 3.2%, and the breakthrough adsorbent amount of H2S was 1.8%.
[0063] Example 6
[0064] 10 kg of 13X, 15 kg of pseudo-boehmite, 15 kg of alumina and 0.3 kg of sesbania powder were powdered and mixed evenly, and then 5 kg of HNO3 aqueous solution (3 wt%) was added and kneaded. After kneading, the mixture was extruded into strips and dried at 120°C for 12 hours. The extruded strips were calcined at 400°C for 5 hours to obtain the original adsorbent particles. 10 kg of the original adsorbent particles were exchanged with 50 kg of 0.4 wt% NaOH solution for 3 hours, filtered and dried at 100°C to obtain the adsorbent. The adsorbent B acid / L acid was 0.06, and the 300°C 1-hexene conversion rate was 0.8%. This shows that after the alkaline solution exchange, the B acid content of the sample was reduced, the 1-hexene conversion rate was low, and the adsorbent surface activity was low.
[0065] Determination of the adsorption amount of NH3 and H2S on the adsorbent: 5g of adsorbent was loaded into a fixed bed reactor, and nitrogen containing 1000ppmNH3 and 1000ppmH2S was used as raw gas respectively. The room temperature was 20℃, normal pressure, and the flow rate was 100ml / min. The content of H2S and NH3 in the outlet gas was determined by a sulfur-nitrogen analyzer. When the content of NH3 and H2S in the outlet gas exceeded 1ppm, it was regarded as adsorbent breakthrough. The breakthrough adsorption amount of NH3 calculated by the breakthrough curve was 3.1%, and the breakthrough adsorbent amount of H2S was 1.8%.
[0066] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An adsorbent, characterized in that: The adsorbent contains: metal components, molecular sieves, pseudo-boehmite and alumina, the B acid / L acid ratio is below 0.1, the metal components are selected from alkali metal components and / or alkaline earth metal components; the adsorbent contains: 0.002-1% by weight of the metal components calculated as metal oxides, 5-30% by weight of the molecular sieves, 20-50% by weight of the pseudo-boehmite, and 20-50% by weight of the alumina; the molecular sieves are selected from one or more of X-type molecular sieves and Y-type molecular sieves.
2. The adsorbent according to claim 1, wherein The B acid / L acid ratio of the adsorbent is 0.001-0.
095.
3. The adsorbent according to claim 2, wherein The B acid / L acid ratio of the adsorbent is 0.03-0.
08.
4. The adsorbent according to any one of claims 1 to 3, wherein The adsorbent contains: 0.01-0.8 weight % of metal component calculated as metal oxide, 10-25 weight % of molecular sieve, 30-45 weight % of pseudo-boehmite, and 30-45 weight % of aluminum oxide.
5. The adsorbent according to any one of claims 1 to 3, wherein The metal component is selected from one or more of sodium, potassium and calcium; and / or The molecular sieve is selected from one or more of 13X molecular sieve and NaY molecular sieve.
6. The method for preparing the adsorbent according to any one of claims 1 to 5, characterized in that: The method includes: 1) kneading and extruding molecular sieve, pseudo-boehmite, alumina, peptizing agent and extrusion aid, drying and calcining to obtain adsorbent original particles A; 2) Add the adsorbent original particles A to a solution containing an alkali metal component compound and / or an alkaline earth metal component compound, perform ion exchange, filter, wash and dry to obtain the adsorbent.
7. The preparation method according to claim 6, wherein: In step 1), The calcination conditions include: a temperature of 200 to 400°C; a time of 2 to 10 hours; and / or In step 2), Drying conditions include: temperature of 50 to 150°C; and / or The conditions for ion exchange include: ion exchange at room temperature for 2 to 5 hours.
8. The preparation method according to claim 7, wherein: In step 1), The calcination conditions include: a temperature of 300 to 350° C. and a calcination time of 4 to 6 hours.
9. The preparation method according to any one of claims 6 to 8, wherein: The alkali metal component compound and / or alkaline earth metal component compound is selected from one or more of nitrates, carbonates, acetates and hydroxides.
10. The preparation method according to claim 9, wherein: The alkali metal component compound and / or alkaline earth metal component compound is selected from sodium hydroxide.
11. The preparation method according to any one of claims 6 to 8, wherein: The solid-liquid mass ratio of the adsorbent original particles A to the solution containing the alkali metal component compound and / or the alkaline earth metal component compound is 0.3-0.1, and the concentration of the solution containing the alkali metal component compound and / or the alkaline earth metal component compound is 0.02-0.5% by weight.
12. The preparation method according to claim 11, wherein The concentration of the solution containing the alkali metal component compound and / or the alkaline earth metal component compound is 0.1 to 0.4% by weight.
13. The preparation method according to any one of claims 6 to 8, wherein: a) the preparation of the pseudo-boehmite comprises: adding 0.5 mol / L to 1.5 mol / L sodium aluminate solution and 0.5 mol / L to 1.5 mol / L nitric acid solution in parallel, controlling the reaction pH to 6 to 8, the reaction temperature to 40 to 90° C., the reaction time to 0.5 to 3 hours, obtaining a precipitate, washing and drying the precipitate to obtain the pseudo-boehmite; b) The preparation of the alumina comprises: uniformly mixing pseudo-boehmite and polyacrylic acid solution, drying, and calcining.
14. The preparation method according to claim 13, wherein: The preparation of the pseudo-boehmite comprises: adding 0.5 mol / L to 1.5 mol / L sodium aluminate solution and 0.5 mol / L to 1.5 mol / L nitric acid solution in parallel, controlling the reaction pH to 6 to 8, the reaction temperature to 40 to 90° C., the reaction time to 0.5 to 3 hours, obtaining a precipitate, and washing and drying the precipitate.
15. The preparation method according to claim 13, wherein: The mass concentration of the polyacrylic acid solution in step b) is 0.5-1.5%, and the solid-liquid mass ratio of pseudo-boehmite to the polyacrylic acid solution is 1:0.5-1.
5.
16. Use of the adsorbent according to any one of claims 1 to 5 for removing polar compounds from olefins.
17. The use according to claim 16, wherein: The olefin is a C2-C4 olefin, and the polar compound is selected from one or more of H2O, methanol, ammonia, H2S and COS.
18. The use according to claim 17; wherein The olefin is one or more of ethylene, propylene and butene.
Citation Information
Patent Citations
Modified 13X zeolite molecular sieve oxynitride purification catalyst and preparation method thereof
CN102451746A
Method for removing oxygen-containing compound in hydrocarbon stream
CN103418164B
Method for preparing denitrifying adsorbent
CN105457600A
Preparation method of absorbent used for removing impurities from olefin flows
CN102921373A
AU9714101A